Growth of carbon nanomaterial on granular activated carbon - Onundi, Yusuf Bamidele; Al-Mamun, Abdullah; Al-Khatib, Ma'an Fahmi Rashid; Ahmed, Yehya M. (Trans Tech Publications Ltd., Switzerland, 2011)
Since the discovery of carbon nanotubes (CNT) and subsequent Carbon Nanomaterials (CNMs), there has been an ever increased academic and industrial interest on there various fields of application due to their exceptional mechanical and electrical properties. In this work, granular activated carbon (GAC) made from palm Kernel shell (PKS) of mesh size 8x12 was impregnated with nickel as substrate catalyst for the growth of Carbon Nanomaterials (CNMs) in a chemical decomposition (CVD) reactor. Various percentage by weight of the nickel (1%, 3%, 5% and 7%) were impregnated on the GAC surface for CNM growth. The CNM growth took place at a fixed reaction temperature and gas flow rates for both the hydrogen gas and carbon source. Characterization of the novel composite material was carried out by using SEM, FESEM and TEM. The results show that growth was successful as at 1% nickel impregnation, while a denser network distribution and rougher surface of CNM was observed at 7% nickel. The growth of CNMs on a larger substrate GAC should make handling of the CNMs easier and it is expected to also open new doors of application in water treatment and oil refining.